Characterization of cellulose bridging pattern in transformer oil using feature extraction technique - Mustafa N.B.A.; Ramasamy I.D.; Nordin F.H.; Ali N.H.N.; Zainuddin H.; Daud M.M. (Institute of Electrical and Electronics Engineers Inc., 2023)
Cellulose; Deterioration; Extraction; Insulating oil; Insulation; Oil filled transformers; Textures; Cellulose bridging; Early prediction; Electrical insulating properties; Feature descriptors; Feature extraction techniques; Features extraction; Highest temperature; Image processing tools; Shape features; Texture features; Feature extraction; Arching; Cellulose; Extraction; Formation; Images; Index Terms; Insulating Oil; Thickness